Acute administration of beta-caryophyllene prevents endocannabinoid system activation during transient common carotid artery occlusion and reperfusion - Poddighe, Laura (Lipids Health Dis, 2018)
BACKGROUND: The transient global cerebral hypoperfusion/reperfusion achieved by induction of Bilateral Common Carotid Artery Occlusion followed by Reperfusion (BCCAO/R) has been shown to stimulate early molecular changes that can be easily traced in brain tissue and plasma, and that are indicative of the tissue physiological response to the reperfusion-induced oxidative stress and inflammation. The aim of the present study is to probe the possibility to prevent the molecular changes induced by the BCCAO/R with dietary natural compounds known to possess anti-inflammatory activity, such as the phytocannabinoid beta-caryophyllene (BCP). METHODS: Two groups of adult Wistar rats were used, sham-operated and submitted to BCCAO/R. In both groups, 6 h before surgery, half of the rats were gavage-fed with a single dose of BCP (40 mg/per rat in 300 μl of sunflower oil as vehicle), while the second half were pre-treated with the vehicle alone. HPLC, Western Blot and immunohistochemistry were used to analyze cerebral cortex and plasma. RESULTS: After BCCAO/R, BCP prevented the increase of lipoperoxides occurring in the vehicle-treated rats in both cerebral cortex and plasma. In the frontal cortex, BCP further prevented activation of the endocannabinoid system (ECS), spared the docosahexaenoic acid (DHA), appeared to prevent the increase of cyclooxygenase-2 and increased the peroxisome-proliferator activated receptor-alpha (PPAR-alpha) protein levels, while, in plasma, BCP induced the reduction of arachidonoylethanolamide (AEA) levels as compared to vehicle-treated rats. CONCLUSIONS: Collectively, the pre-treatment with BCP, likely acting as agonist for CB2 and PPAR-alpha receptors, modulates in a beneficial way the ECS activation and the lipoperoxidation, taken as indicative of oxidative stress. Furthermore, our results support the evidence that BCP may be used as a dietary supplement to control the physiological response to the hypoperfusion/reperfusion-induced oxidative stress.